2015
DOI: 10.12693/aphyspola.128.935
|View full text |Cite
|
Sign up to set email alerts
|

Ionization of Short-Lived Isotopes in Spherical Hot Cavities

Abstract: The numerical model of ionization of short-lived nuclides in spherical hot cavities is presented. Two dierent cavity congurations are considered: one of them (the hemispherical one) resembles that known from already existing ion sources while the other (closer to the full sphere) could be more ecient for short-lived isotopes. Changes of ionization eciency with the half-life period as well as with the particle average sticking time are presented and discussed. Inuence of the extraction opening radius on ionizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Some of them focused on thermal ionization in the hot cavity [11,22,23], describing the crucial effect of multiple collisions with the walls of the hot cavity, while other papers presented issues such as vapour transport from the bombarded target to the ionizer [24,25] or the release of nuclides from the walls of the ionizer [26,27]. Various shapes of ionizers were considered in the literature; the most popular being tubular [23,[28][29][30], rarely employed spherical or hemispherical [31][32][33], but also conical [34][35][36], and even the most exotic, resembling a kind of mace with spikes [22]. Recently, a cavity having the shape of a flat disc was considered [37], being a case of tubular ionizer characterized by a very small length compared to its diameter, which results in a large number of particle-wall collisions during the particle's travel to the extraction aperture.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of them focused on thermal ionization in the hot cavity [11,22,23], describing the crucial effect of multiple collisions with the walls of the hot cavity, while other papers presented issues such as vapour transport from the bombarded target to the ionizer [24,25] or the release of nuclides from the walls of the ionizer [26,27]. Various shapes of ionizers were considered in the literature; the most popular being tubular [23,[28][29][30], rarely employed spherical or hemispherical [31][32][33], but also conical [34][35][36], and even the most exotic, resembling a kind of mace with spikes [22]. Recently, a cavity having the shape of a flat disc was considered [37], being a case of tubular ionizer characterized by a very small length compared to its diameter, which results in a large number of particle-wall collisions during the particle's travel to the extraction aperture.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a cavity having the shape of a flat disc was considered [37], being a case of tubular ionizer characterized by a very small length compared to its diameter, which results in a large number of particle-wall collisions during the particle's travel to the extraction aperture. Some versions of the numerical models were only suitable for stable (non-radioactive) nuclides, whilst the latter were upgraded to take into account the effects of radioactive decay and delays due to diffusion and effusion [32,38]. It was also shown that in the case of hard-to-ionize nuclides, the other ionization mechanism included in the model, i.e., electron ionization, could also give a substantial contribution to the total ion source yield [28,29,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radioactive decay and delays, due to the nuclide diffusion towards the target surface and sticking to hot walls and effusion, were implemented [20,27] which made the model applicable also for short-lived isotopes. The most popular tubular cavities were considered as first, but then the model was extended also to spherical and hemispherical cavities [20,28,29]. Recently [30,31] the hot cavity having a shape of a truncated cone has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The model enabled studies of ion source efficiency as a function of many factors, like ioniser temperature, extraction voltage, timescales governing diffusion and effusion processes, as well as radioactive decay half-life. The ionisation calculations were performed for both tubular ioniser geometry and the spherical shapes [17,18], which * corresponding author; e-mail: mturek@kft.umcs.lublin.pl proved to be very effective, especially in the case of shortlived isotopes.…”
Section: Introductionmentioning
confidence: 99%